EFFECTS OF LASER RADIATION ON THE KINETICS OF PHYSICAL AND CHEMICAL TRANSFORMATION OF POLYMERS - , Ф. С., С. Е. (Municipal economy of cities. Series: «Economy science», 2013)
Consider physical modification of polymers laser to reduce their flammability shows experimental research methods and analysis UV and IR spectra film epoxy compositions.